2002
DOI: 10.1037/0021-9010.87.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Development and test of a model linking safety-specific transformational leadership and occupational safety.

Abstract: The authors developed, tested, and replicated a model in which safety-specific transformational leadership predicted occupational injuries in 2 separate studies. Data from 174 restaurant workers (M age = 26.75 years, range = 15-64) were analyzed using structural equation modeling (LISREL 8; K. G. Jöreskog & D. Sörbom, 1993) and provided strong support for a model whereby safety-specific transformational leadership predicted occupational injuries through the effects of perceived safety climate, safety conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
747
3
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 818 publications
(801 citation statements)
references
References 44 publications
39
747
3
12
Order By: Relevance
“…A strong organizational "safety first" philosophy impacts members' beliefs and attitudes towards product safety, and consequently, leads to its high priority and adoption of processes and practices that support the organization's commitment to product safety. Moreover, this espousal of occupational health and safety culture has been linked to safer work behaviors (Hofmann & Stetzer, 1996;Varon & Mattila, 2000) and fewer employee injuries (Barling et al, 2002;Hofmann & Stetzer, 1996;Mearns et al, 2003;Zohar, 1980). The literature on product safety culture is still sparse.…”
Section: Espoused Valuesmentioning
confidence: 99%
“…A strong organizational "safety first" philosophy impacts members' beliefs and attitudes towards product safety, and consequently, leads to its high priority and adoption of processes and practices that support the organization's commitment to product safety. Moreover, this espousal of occupational health and safety culture has been linked to safer work behaviors (Hofmann & Stetzer, 1996;Varon & Mattila, 2000) and fewer employee injuries (Barling et al, 2002;Hofmann & Stetzer, 1996;Mearns et al, 2003;Zohar, 1980). The literature on product safety culture is still sparse.…”
Section: Espoused Valuesmentioning
confidence: 99%
“…Second, employees likely hide unsafe behavior from their supervisors, therefore causing supervisors to lack the awareness necessaiy to accurately assess the prevalence of unsafe behavior by their employees. Fina lly, self-report data is not scant in the unsafe behavior literature (e.g., Barling et al, 2002;Newnam et al, 2008), and Lajunen and Summala (2003) found self-report safety data to be significantly associated with objective safety data.…”
Section: Individual-level Measuresmentioning
confidence: 99%
“…However, recent studies found that 'resource comes later' but the management attitude plays the leading role for organizational adoption of OHS, especially as the initial stage (Barling et al, 2002).…”
Section: H3mentioning
confidence: 99%
“…Barling et al (2002) argue that top management commitment is extremely influential for organizations to adopt OHS policy and practices. Precisely, in education industry, top management commitment is found as the most important factor for OHS implementation (Wu et al, 2008).…”
Section: H3mentioning
confidence: 99%